Towards health security in Nigeria in 2050: Strategies for managing violent conflicts, humanitarian emergencies and natural disasters (2019)
Introduction: Avery important but neglected aspect of healthcare delivery in Nigeria is the management of outcomes of violent conflicts, humanitarian emergencies and natural disasters within the framework of national health policy and available healthcare infrastructures and services. Although this aspect of national healthcare is often neglected in national healthcare discourses, it constitutes very crucial part of determinants of average life expectancy of citizens and general wellbeing of the population. Methods: Library and archival materials constituted the sources of data for the paper. Policy documents, reports and analysis of the health condition of Nigerians in relation to management of the outcome of natural, humanitarian emergences and violent conflicts published by non-governmental organisations, government bodies and international agencies were content analysed. Results: This article attempts to characterise the current condition of humanitarian emergencies and disaster management readiness from the purview of the health sector through assessment of the available emergency management and trauma facilities. It projects into the future situation of this aspect of national healthcare by the year 2050 when the population of the country is expected to double. It is observed that if the current despicable condition of the health facilities in the sector is not addressed, the situation is likely to become worse by the projected year and could portend dire situation for Nigeria. Conclusion: The paper makes prescriptions on remedies in terms of human resources development, erection of relevant infrastructures and acquisition of necessary equipment that could boost that aspect of national healthcare. Above all, there is need for strong leadership and political commitment to achieve qualitative improvement in the focused sector of the healthcare before year 2050